A framework for fostering the quality of HEIs: data collection, evaluation, indication and validation. (2016) - Al-Hemyari, Zuhair A.; Al-Sarmi, Abdullah M.
It is well known that the concept of quality in higher education is a compound concept which depends on many dimensions and factors. Moreover, there exist many common quality approaches which are used to assess the quality and performance of HEIs. In the last decade, the performance and quality measurement approaches of institutional activities have become critical factors in society knowledge, and hence institutions have adopted different approaches to achieve high quality and performance. This paper elaborates on the processes and applications of the quality excellence models in higher education, contributed to the science and knowledge of quality/performance of HEIs. In addition to what was already mentioned, different methods and models of quality management of HEIs were reviewed and the paper will be particularly focused on the contributions of two well-known methods of quality management. Also, this paper will propose a detailed model of objectives oriented to assess the quality of HEIs and hence to contribute to the science and knowledge of the quality of HEIs. The data is collected and analysed. The findings have shown that the results have a considerable gain in all statistical measures. Conclusions, recommendations and limitations were reported and discussed.